The Effect of Air Quality on Environmental Hue Due To The Level of Traffic Congestion at Intersection Dinoyo and Simpang Sardo, Malang City - Sriliani Surbakti; Nusa Sebayang; Maria Leontina Lidya Tauk (Green Publisher Indonesia, 2025)
Therefore, from the performance results of the Dinoyo intersection and the Sardo intersection of Malang city which refers to the 2023 Indonesia Road Capacity Guidelines, and the air quality is guided by the Regulation of the Minister of Environment and Forestry No. 14 of 2020, the degree of saturation for 3 days of observation is still more than 0.85 with the service level E due to the service level is still poor, so it is necessary to plan improvements at the Dinoyo intersection of the signalized intersection with geometric widening while in The unsignaled junction of the Sardo junction is planned with road geometry on each arm of the road. The largest delay value is 24.175 sec/smp so that the level of intersection service produced is at least D., while at the Sardo junction the degree of saturation for 3 days of observation is still more than 0.85 with service levels B and C. and the air quality is measured at 06.00 – 07.00 with a delay value of 39.765 sec/smp, then the particulate concentration obtained NO2 is the ISPU value of 21.170 (18 ppm), SO2 ISPU value: 47.866 (19 ppm), C0 ISPU value: 15.609 (1090 ppm). The results of the air quality analysis show that the CO air quality parameter has a great influence on the environmental profile and the decline in public health due to air pollution due to high gas emissions from high vehicle volumes. https://hardtechgroup.net/menelusuri-dimensi-slot-petualangan-di-kasino-online-indonesia/ https://xoompages.com/zeus-slot-gacor-memahami-rahasia-kemenangan-di-permainan-kasino-online/ https://barcelonajerseys.net/panduan-lengkap-slot-gacor-menyelami-strategi-dan-taktik-untuk-menang-di-kasino-online/ https://wedoassignmenthelp.com/menemukan-slot-gacor-hari-ini-strategi-dan-tips-untuk-memaksimalkan-kemenangan-anda-di-kasino-online/ https://freepostarticles.com/sejarah-terkini-dan-relevansi-martha-di-dunia-kasino-online/ https://onestylishday.com/menelusuri-dimensi-tersembunyi-dalam-permainan-slot-di-kasino-online-indonesia/ https://www.budapestresources.com/mengenal-fenomena-slot-gacor-rahasia-di-balik-kesuksesan-permainan-kasino-online/ https://thelimitsofcontrol-laura.com/panduan-lengkap-zeus-slot-gacor-untuk-pemain-online-casino-di-indonesia/ https://maquinasdecosertop.com/slot-gacor-hari-ini-menyelami-dunia-mesin-slot-yang-menguntungkan/ https://whitecrack.com/sejarah-martha-evolusi-di-dunia-kasino-online/